Therapeutic Success in Amoebic and Pyogenic Liver Abscesses - Azhari Gani; Iskandar Zakaria (Britain International for Academic Research (BIAR) Publisher, 2021)
A 52 year old male patient presented with complaints of upper right abdominal pain since 1 month ago, worsening in the last 1 day. Fever has been complained of since 1 month ago, fever fluctuates indefinitely, comes down with fever-reducing drugs, complained of weakness. There is nausea and vomiting, vomiting 1-2 times per day, black vomit like coffee is not there. Complained about weight loss. BAK is like strong tea. Liquid defecation has been complained of since 5 weeks ago, initially liquid defecation was accompanied by mucus and blood with a frequency of 3-4 times per day for 3 days, at that time the patient went to the health center and complaints were reduced and now liquid CHAPTER 1-2 times a day is yellow, liquid, no mucus, no blood for the past 1 month. The patient is an agricultural instructor with his daily activities going down to the farm. History. History of diabetes mellitus denied. Patients diagnosed with multiple pyogenic liver abscess were treated at RSUDZA and received bed rest therapy, 1800 kcal / day soft food diet, IVFD NaCl 0.9% 20 drops per macro minute, metronidazole drip 500 mg every 8 hours, ciprofloxacin 2x 500 mg, intravenously paracetamol 1 gram every 8 hours. The patient was treated for 17 days, on the 10th day of hospitalization the patient was performed a laparotomy and multiple incisions of the liver abscess, purulent abscess fluid mixed with blood. The abscess fluid was cultured as a result of Entamoeba Colli, and metronidazole antibiotic therapy was continued. During treatment, the patient experienced clinical improvement, the patient was opened surgical sutures on the 10th and 15th day after laparotomy, the surgical wound improved, the patient experienced clinical improvement, currently the patient is still a control at the Internal Medicine and Surgery Department at Cut Nyak Dhien Meulaboh Hospital.